El proceso de diagnostico en el proyecto mandioca del Paraguay - Llamas G., P.A. de (International Center for Tropical Agriculture, 1989)
Background information is given on the Paraguayan cassava project, which aims at increasing cassava production and productivity through the use of improved technology while improving the living standards of cassava growers in Caaguazu and Paraguari. Different information retrieval procedures were used to collect basic information on existing production systems; these included a survey which helped identify main production constraints and a physical characterization of production zones; a production questionnaire replied by 100 farmers in each region, which yielded valuable information on land availability, soil impoverishment, planting times, labor, and traditional cultural practices; and a cassava starch production study which consisted in 20 interviews, 10 in each region, which helped identify processing problems, technologies and equipment used. The latter study indicated the existence of 3 levels of production, namely completely rudimentary, semimechanized, and mechanized. A marketing survey was also carried out at the wholesaler, retailer, and consumer levels. Information was collected on commercialization channels, percentage distribution among participants, vol. and price paid/received, margins for middlemen, product characteristics considered important to retailers and consumers, sites of purchase according to income strata, and economic losses due to deterioration. (CIAT)